2021
DOI: 10.1016/j.clnu.2020.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency leads to reduced interleukin-2 production by active gene silencing due to enhanced CREMα expression in T cells

Abstract: Background & Aims:The micronutrient zinc is essential for proper immune function. Consequently, zinc deficiency leads to impaired immune function, as seen in decreased secretion of interleukin (IL)-2 by T cells.Although this association has been known since the late 1980s, the underlying molecular mechanisms are still unknown. Zinc deficiency and reduced IL-2 levels are especially found in the elderly, which in turn are prone to chronic diseases. Here, we describe a new molecular link between zinc deficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…In vitro investigation revealed that Zn deficiency increased CREMα expression (48) . IL-2 has dual effects on inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro investigation revealed that Zn deficiency increased CREMα expression (48) . IL-2 has dual effects on inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its high expression inhibits IL-2 transcription (48) . In-vitro investigation revealed that Zn deficiency increased CREMα expression (48) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that zinc levels modulate IL‐2 expression, providing another explanation of altered CD25 expression. [ 56 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Research Council (NRC, 1994), the requirement of zinc for broilers is 40.0 ppm; approximately 100 ppm zinc from different sources is typically added to feed to optimize animal performance [ 13 , 14 ]. The underlying mechanisms could be attributed to altered intestinal histomorphology and reduced inflammation and oxidative stress [ 15 , 16 ] resulting in improved growth of broilers. Increasing lines of evidence indicate that zinc is redistributed in animals under conditions of oxidative stress and immune challenge [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%